Trauma and Its Ancient Literary Representation: Mark 5,1–20 - Hogeterp, Albert L. A. (Zeitschrift für die neutestamentliche Wissenschaft, 2020)
This article revisits Mark 5,1-20 from the perspective of trauma theory, in light of historical contexts of Gerasa’s collective trauma and the cultural contexts of ancient perceptions of demons and their exorcism. The interplay between individual and collective levels of the story sheds light on symbolic overtones of an unresolved trauma about Roman military presence in the country of the Gerasenes. The story represents this trauma through literary indirection, including not only the enigmatic relation between “Legion” and the drowning swine, but also the paradoxical contrasts between individual and collective requests to Jesus. Mark 5,1-20 evokes meanings not only as pre-Markan tradition, but also as Markan redaction which intersect in crucial ways with the prelude to Jerusalem’s destruction (68-70 C.E.).